2020
DOI: 10.1016/j.clinimag.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous subcutaneous emphysema and pneumomediastinum in non-intubated patients with COVID-19

Abstract: Purpose We describe the presenting characteristics and hospital course of 11 novel coronavirus (COVID-19) patients who developed spontaneous subcutaneous emphysema (SE) with or without pneumomediastinum (SPM) in the absence of prior mechanical ventilation. Materials and methods A total of 11 non-intubated COVID-19 patients (8 male and 3 female, median age 61 years) developed SE and SPM between March 15 and April 30, 2020 at a multi-center urban health system in New York… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 37 publications
(38 reference statements)
3
68
1
4
Order By: Relevance
“…Our study found that NIV failed in preventing mechanical ventilation in 38% as compared with 28% in a study by Manna et al who reported that patients who failed NIV were older, had a higher respiratory rate, PaCO2 and D-dimer levels before NIV, and higher minute ventilation and ventilatory ratio on the first day of NIV [ 22 ]. In our study, patients receiving HFNC were few in number, and since we employed an HFNC/NIV alternating strategy on most patients, comparison between the two modalities was not feasible.…”
Section: Discussionmentioning
confidence: 78%
“…Our study found that NIV failed in preventing mechanical ventilation in 38% as compared with 28% in a study by Manna et al who reported that patients who failed NIV were older, had a higher respiratory rate, PaCO2 and D-dimer levels before NIV, and higher minute ventilation and ventilatory ratio on the first day of NIV [ 22 ]. In our study, patients receiving HFNC were few in number, and since we employed an HFNC/NIV alternating strategy on most patients, comparison between the two modalities was not feasible.…”
Section: Discussionmentioning
confidence: 78%
“… 2 Recently a few authors have also reported this in Covid-19 patients. 3 , 4 In this communication we report an occurrence of bilateral subcutaneous emphysema in a patient of COVID-19 pneumonia without pneumothorax and pneumomediastinum having no previous history of respiratory disease.…”
Section: Introductionmentioning
confidence: 80%
“…studied eleven non-intubated patients of COVID-19 with spontaneous pneumomediastinum and subcutaneous emphysema. All these patients were non-smokers, among which five were diabetic and four patients expired during their hospital stay [ 14 ]. This is similar to the prognosis and data of our patient.…”
Section: Discussionmentioning
confidence: 99%